2007
DOI: 10.1002/ijc.22488
|View full text |Cite
|
Sign up to set email alerts
|

Impact of disseminated tumor cells in bone marrow at diagnosis in patients with nonmetastatic prostate cancer treated by definitive radiotherapy

Abstract: The purpose of this study was to explore whether detection of disseminated tumor cells (DTCs) in bone marrow (BM) of nonmetastatic prostate cancer (PC) was associated with other clinical or histopathological factors at diagnoses or clinical outcome subsequent to definitive radiotherapy (RT). We evaluated BM aspirates from 272 cT 1-4 pN 0 M 0 PC patients by immunocytochemistry employing anticytokeratin antibodies (AE1/AE3). BM-status was compared with clinical and histopathological parameters. Longterm clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 43 publications
2
31
0
Order By: Relevance
“…Although a DTC-positive BM status was associated with grading and increased risk of metastasis, the study by Berg et al (2007) 181 on 266 patients did not find a correlation of DTC detection and survival. Most recently, K€ ollermann et al 179 reported on the prognostic relevance of DTC in BM found in 86/193 (44.6%) patients with clinically localized prostate cancer submitted to neoadjuvant hormonal therapy followed by radical prostatectomy and a median follow-up of 44 months.…”
Section: Prostate Cancermentioning
confidence: 84%
See 1 more Smart Citation
“…Although a DTC-positive BM status was associated with grading and increased risk of metastasis, the study by Berg et al (2007) 181 on 266 patients did not find a correlation of DTC detection and survival. Most recently, K€ ollermann et al 179 reported on the prognostic relevance of DTC in BM found in 86/193 (44.6%) patients with clinically localized prostate cancer submitted to neoadjuvant hormonal therapy followed by radical prostatectomy and a median follow-up of 44 months.…”
Section: Prostate Cancermentioning
confidence: 84%
“…Spread of DTC seems to be linked to histological differentiation of the primary tumor. 61,181 Moreover, while in some studies DTC detection was not associated with initial PSA concentration in the serum of prostate cancer patients, 177,179 a correlation of DTC measurement to early PSA recurrence was shown by 2 studies. 179,180 Weckermann et al 180 analyzed 82 patients and observed that the mean time to PSA increase was shorter in patients with DTC-positive compared with DTC-negative BM samples.…”
Section: Prostate Cancermentioning
confidence: 99%
“…CTC are thought to arise through detachment from the primary tumor, intravasation and spread to distant sites as micrometastases, which may progress to overt clinical metastases [4]. Significantly, a burst of recent evidence has revealed that CTC levels are strongly predictive of metastasis and poor disease prognosis in lung [5], breast [6], colon [7], esophageal [8], and particularly prostate cancers [9], in which the presence of detectable CTC has been correlated with advanced cancer stage in several studies [10][11][12][13]. Previous in vivo experiments from our laboratory also demonstrated that high numbers of CTC in an orthotopic mouse model of prostate cancer were associated with increased metastasis to the lung [14].…”
Section: Introductionmentioning
confidence: 98%
“…Berg et al have shown that patients given radical EBRT for prostate cancer with a GS of at least 4 + 3 = 7 and a positive bone marrow for CTCs have double the risk of developing biochemical recurrence [26]. Thus, it would be interesting to analyse patients with biochemical recurrence after RP for CTCs to determine whether the presence of CTCs could predict patients at risk of being resistant to salvage EBRT.…”
Section: Discussionmentioning
confidence: 99%